Missing stillbirth data: a hospital based study - Kusre, Giriraj; Baruah, Jenita (International Journal Of Community Medicine And Public Health, 2016)
Background: Stillbirths has remained a neglected issue, invisible in policies and programmes, underfinanced and in urgent need of attention. In India inadequacy has been observed in monitoring of the time and cause of death of unborn infants. So the present study attempts to assess the problem of underreporting and completeness of the information of data in stillbirth registry in a tertiary care hospital in Northeast India and analyse the cause behind it. Methods: The study was carried out from January 2016 to June 2016. Case sheets related with stillbirth born during the period of study were retrieved, detail information regarding address of the mother, her age, gestational age, gravida and parity, medical and obstetrical condition leading to stillbirth, gestational age, weight, sex and condition of the fetus at the time of birth (macerated or fresh) were noted. The information was compared with the data entered in stillbirth registry. Process of entry of stillbirth data was observed and interns and PGs who entered the data were interviewed using a semi structured proforma. Results: Stillbirth rate for the hospital was 27.95/1000 births. All information regarding stillbirth except information regarding condition of the fetus (macerated vs. fresh) were present in case sheet, but only 59.64% of stillbirth had mention of their sex and weight in the register. Conclusions:Lack of training, hectic activity in labour rooms and absence of dedicated staff results in incomplete entry of stillbirth data in the register.